The impact of public debt on economic growth in South Africa : a cointegration approach - Masoga, Mamokgaetji Marius (University of Limpopo, 2018)
The burden of public debt is an economic issue, dominating debates in different sectors of our society. The post financial crisis era has been marked with an increasing level of public debt at international, national and sub-national level. The study investigates if public debt can affect economic growth in South Africa, for the period 1995 to 2016. The results for Johansen test of cointegration signposted the existence of cointegration among variables observed in this study. The trace statistic and max-eigen value complimented each other to confirm the cointegration, thus, showing a long run relationship. Furthermore, the Vector Error Correction Model (VECM) is applied to achieve the objectives of the study, complemented by other econometric tests such as, Granger causality, impulse response function and variance decomposition. The VECM results revealed the existence of a short run relationship between public debt and economic growth. Granger causality results have shown that public debt can Granger cause economic growth, and there is bi-direction relationship between the two variables. The results for Variance Decomposition indicate that, a shock to public debt causes 1.509115 % fluctuation in economic growth in the second quarter. In the fourth quarter, a shock to public debt account for 16.39628 % fluctuations in economic growth. This shows that, as time goes on, a shock to public debt account for a high percent of fluctuation in economic growth. The Impulse Response Function has shown that, the period of ten quarters marks a negative response of economic growth to public debt. Thus, one standard deviation shock in public debt will inversely affect economic growth. The diagnostic tests such as serial correlation and heteroskedasticity bode well for the model because, neither serial correlation nor heteroskedasticity has been found. Moreover, the model has shown that the residuals are normally distributed, and also the stability of the model has been confirmed. The study recommends that, since South Africa is a capital scarce country, it is encouraged to borrow so that there is an increase in the accumulation of capital. However, the later stage of borrowing marked with high debt will lead to subdued economic growth.
Thesis (M.Com (Economics)) --University of Limpopo, 2018
Keywords: Public debt; External debt; Internal debt; Economic growth; South Africa; Economic growth; Public debt